DESKRIPSI PELAKSANAAN PEMBELAJARAN E-LEARNING DENGAN MODEL PROBLEM BASED LEARNING DITINJAU DARI ASPEK MOTIVASI BELAJAR SISWA PADA MASA NEW NORMAL COVID-19 - Br Purba, Salmiah; Yustina, Yustina; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study to describe the infrastructure readiness for the implementation of e-learning and the relationship between e-learning and the Problem Based Learning model in terms of student motivation in the new normal covid-19 period. This type of research is descriptive research. The population in this study is class X SMA Islam As-shofa Pekanbaru with a random sampling technique, amounting to 24 students. The data collection technique is a survey using an observation sheet. Based on observations, the implementation of e-learning at As-Shofa Islamic High School is adequate, with facilities ranging from software consisting of laptops with a percentage of 92 (very high category), computers with a percentage of 58 (medium category) and cellphones with a percentage of 100. (very high category), while the hardware consisting of wifi with a percentage of 79 (high category), internet quota with a percentage of 100 (very high category) and a learning community in the form of whatsapp and classrooms with a percentage of 100 (very high category), so that it can support online learning process. The description of the implementation of learning is carried out by linking e-learning activities according to the PBL model syntax in which there are aspects of student learning motivation.Key Words: e-learning, PBL model, learning motivation